Re-Analysis of the Prototype Structure of Earthquake-Resistant Flats Built in the Seismic Mitigation Area Central of Borneo - Su, Johan; Kraugusteeliana, Kraugusteeliana; Irwansyah, Defi (International Journal of Engineering, Science and Information Technology, 2023)
Indonesia is an earthquake-prone area; to reduce the risk of disasters, it is necessary to construct earthquake-resistant buildings. The concept of earthquake-resistant buildings attempts to make all structural elements into a unified whole that is not easily collapsed by an earthquake. In general, the planning of the structure of an apartment is made of a prototype whose structure is calculated to be earthquake-resistant. However, not all flats are built in earthquake-prone areas. One is in Central Borneo Province, which is not prone to earthquakes. The research aims to determine the comparison of the dimensions and reinforcement requirements on the prototype with Kriteria  Desain  Struktur (KDS) 'BC' Structural Design Criteria compared to structural planning in the Central Borneo Seismic Mitigation Area. Design standards refer to SNI 1727:2013, SNI 2847:2013, SNI 2847-2019, and SNI 1726-2019. The building being studied is the Type 36 Prototype Flat (5 floors) using concrete fc' 22.8 MPa and reinforcing steel my 420 MPa. Research on Columns and Beams' superstructure includes the design of the structural dimensions and reinforcement requirements. Structural dimensions and reinforcement area will be designed efficiently and declared safe by controlling the reinforcement ratio(p). Structural dimensional limitations. Structural calculation analysis using the  ETABS computer application.